The Correlation between Marketing Factors and the Marketing Effectiveness of Student Products - Gabryaldo, Igods; Diansari, Pipi; Putri, Ariella Ramadhani; Imelda, Andi; Syastiawan, Andi; Syamsi, Zulfikar (Tarjih : Agribusiness Development Journal, 2025)
Marketing is one of the main pillars in the business world that determines the success of a product or service in the market. This study aims to analyze the relationship between marketing frequency, understanding of marketing concepts, implementation of marketing strategies, and digital marketing knowledge with the marketing effectiveness of student products. The research was conducted at the D4 Agribusiness Food Study Program, Hasanuddin University. The sample was selected using a purposive sampling technique, targeting students who had participated in marketing-based practical courses. The sample size for this study consisted of 63 students from the D4 Agribusiness Food Study Program. Data were collected through the distribution of questionnaires to the students who served as research respondents. The data obtained from the questionnaire distribution were analyzed using both quantitative and qualitative approaches. The quantitative approach was used to test the relationship between the independent variables—marketing frequency, understanding of marketing concepts, marketing strategies, and digital marketing knowledge—and the dependent variable, marketing effectiveness, using Spearman Rank correlation analysis. Meanwhile, the qualitative approach was used to describe the quantitative findings. The results of this study conclude that the understanding of marketing concepts has a significant and the strongest correlation with the effectiveness of student product marketing, compared to marketing strategies and digital marketing knowledge. In contrast, marketing frequency does not show a significant relationship with marketing effectiveness. These findings imply that study programs should place greater focus on strengthening students’ understanding of marketing concepts in courses related to product marketing.